Tingkat Kepuasan Pasien Rawat Inap Dengan Anemia Pada CKD on HD Dapat Dipengaruhi Oleh Perilaku Caring Perawat: Satisfaction of Hospitalized Patients with Anemia in CKD on HD can be Influenced by Nurse Caring Behavior - Nurtika, Baiq Laely (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Nurses' caring behavior is the main focus in providing nursing care so that satisfaction from the care process is realized; the condition of anemic patients with CKD on HD requires attention and support from families and nurses who care for patients in hospitals. Methods: This type of research is quantitative descriptive with a cross-sectional approach. The sampling technique used was total sampling with 39 patients in the inpatient room at Prikasih Hospital. Then the data were analyzed using the Chi-Square test. Results: Most of the patients thought that the nurse cared (87.2%) and most of them were satisfied (79.5%). The results of the Chi-Square test carried out obtained the value of Value = 0.049 which means <0.05 then Ho is rejected then Ha is accepted. With an OR of 8700, it means that nurses who behave caring will lead to patient satisfaction compared to non-caring behavior. Discussion: There is a significant relationship between the caring behavior of nurses and the level of satisfaction of anemic patients with CKD on HD in the inpatient room at Prikasih Hospital Pondok Labu in 2021.